2021
DOI: 10.1007/s00262-021-02976-7
|View full text |Cite
|
Sign up to set email alerts
|

T cells, particularly activated CD4+ cells, maintain anti-CD20-mediated NK cell viability and antibody dependent cellular cytotoxicity

Abstract: Anti-CD20 monoclonal antibody (mAb) therapy is a mainstay of therapy for B cell malignancies, however many patients fail to respond or eventually develop resistance. The current understanding of mechanisms responsible for this resistance is limited. When peripheral blood mononuclear cells of healthy donors were cultured with Raji cells for 7 days, rituximab (RTX) induced NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC), enhanced NK cell viability and increased or maintained NK expression of CD5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…NK cells have demonstrated potent anti-tumor efficacy by directly killing cancer cells in preclinical animal models and clinical settings 41,42 . CD4 + T cell derived IL-2 also maintains NK cells for targeting of antibody opsonized tumor cells, such as anti-CD20 antibody coated B cell lymphomas 43 . Furthermore, myeloid cell activation by CD4 + T cell produced IFN- and TNF- leads to tumor cell killing, probably by induced nitric oxide production 44 , upon TAA uptake and presentation by macrophage populations in the TME 45 .…”
Section: Cd4 + T Cells In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…NK cells have demonstrated potent anti-tumor efficacy by directly killing cancer cells in preclinical animal models and clinical settings 41,42 . CD4 + T cell derived IL-2 also maintains NK cells for targeting of antibody opsonized tumor cells, such as anti-CD20 antibody coated B cell lymphomas 43 . Furthermore, myeloid cell activation by CD4 + T cell produced IFN- and TNF- leads to tumor cell killing, probably by induced nitric oxide production 44 , upon TAA uptake and presentation by macrophage populations in the TME 45 .…”
Section: Cd4 + T Cells In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Early studies have provided confirmation of the anti-tumor function of NK cells in defending against tumor metastases ( Larsen, Gao & Basse, 2014 ). Activated CD4+ T cells Additionally, recent evidence has demonstrated that activated CD4 + T cells contribute to the maintenance of NK cell viability and their ability to mediate antibody-dependent cell-mediated cytotoxicity (ADCC) via local IL-2 production ( Wang et al, 2022 ). Furthermore, CD4 + T cells have long been recognized for their critical roles in coordinating of innate and antigen-specific immune responses ( Speiser et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…191,192 Similarly, CD4 + T cell-derived IFN-γ mediates an increase in tumoricidal effectors, monocytemacrophages, which secrete NO to induce remote inflammatory cell death in IFN-unresponsive, MHC-deficient tumor cells. 193 Second, IL-2 produced by CD4 + T cells has been proved to associated with the maintenance and the activation of NK cells, [194][195][196] which could present antitumor effects through direct killing functions in murine models and clinical patients. 197,198 Additionally, it has been reported that CD4 + T cells play a vital role in the induction of humoral responses (Figure 3B).…”
Section: Interaction Of Cd4 + T Cells With Macrophages Nk Cells and B...mentioning
confidence: 99%
“…Second, IL‐2 produced by CD4 + T cells has been proved to associated with the maintenance and the activation of NK cells, 194 , 195 , 196 which could present antitumor effects through direct killing functions in murine models and clinical patients. 197 , 198 …”
Section: Cd4 + T Cell Roles In Antitumor and Antic...mentioning
confidence: 99%